2003
DOI: 10.1093/humrep/deg444
|View full text |Cite
|
Sign up to set email alerts
|

Infertility and preterm delivery, birthweight, and Caesarean section: a study within the Danish National Birth Cohort

Abstract: Infertile women are at higher risk of adverse birth outcomes even if they conceive without treatment. With >10% of babies born to infertile couples, it is important to consider this group as potentially high risk when providing prenatal care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
138
1
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(155 citation statements)
references
References 27 publications
13
138
1
3
Order By: Relevance
“…Zhu et al also observed that the overall prevalence of congenital malformations increased with increasing time to pregnancy (TTP). Zhu's results support our suggestion and that of other investigators [30][31][32] that only subfertile couples are an appropriate control group for ART outcome studies because subfertility, with all its underlying causes, itself creates a risk of MM and other outcomes of concern.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Zhu et al also observed that the overall prevalence of congenital malformations increased with increasing time to pregnancy (TTP). Zhu's results support our suggestion and that of other investigators [30][31][32] that only subfertile couples are an appropriate control group for ART outcome studies because subfertility, with all its underlying causes, itself creates a risk of MM and other outcomes of concern.…”
Section: Introductionsupporting
confidence: 87%
“…Basso and Baird [32] found that an increasing TTP was associated with significantly increased risk of preterm (less than 37 weeks) delivery (PTD). In all primiparous women (treated or untreated) with a TTP of greater than 12 months, the OR for preterm birth was 1.38 (95% CI 1.14-1.69); in the untreated-only subset, the OR was very similar at 1.36 (95% CI 1.08-1.71).…”
Section: Protective Effectmentioning
confidence: 99%
“…Recurrent pregnancy loss is an indicator for increased risk for birth defects, again without regard to the use of ART (31). In two large registry studies (32,33) infertility itself, independent of treatment, appears to be associated with preterm birth and other adverse birth outcomes. The female partners of couples undergoing ART have been found to exhibit an increased frequency of chromosomal abnormalities (34).…”
Section: Discussionmentioning
confidence: 99%
“…Unadjusted analyses suggest a 2-fold increased risk of preeclampsia, placental abruption, Caesarean section, and vacuum extraction, and a 5-fold increased risk of placenta previa in spontaneous singleton pregnancies in women with a history of infertility compared with the general population [7]. Analyses adjusted for age and parity suggest a 1.4-1.8-fold increase in risk for preterm delivery in women requiring greater than 1 year to spontaneously conceive singleton pregnancies, compared with women conceiving without delay [8,9]. A 3-fold increased risk of perinatal mortality has been observed in women with untreated infertility compared to women without infertility after adjusting for potential confounders [10].…”
Section: Introductionmentioning
confidence: 92%